Peningkatan Pengetahuan Dan Skill Anak Di Usia Dini: Melalui Literasi Islamiah - Sultan, Zulkifli; Andriyansah, Andriyansah; Arifin, Andi Harmoko; Pratiwi, Widya Rizky (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
The aim of this community service is to increase knowledge and measure children's abilities in understanding Islamic teachings through literacy. The implementation of PkM is located in the Kamilah housing complex, inhabited by around 200 people, to be precise, the location is in Bojong Sari District, Depok City. This PkM activity is in the form of a competition which is attended by 50 children aged 5 to 10 years. The implementation method consists of 3 steps, the first is the preparation stage by collecting data on the number of participants and making an activity schedule. The second stage is the implementation where participants take part in the competition according to those selected based on previous filling in for willingness. Next, assess the work results of the participants based on the assessment criteria agreed upon by the committee team. The results obtained in this community service are that children are able to know the procedures and rules in Islamic religious teachings such as those related to adab, tajwid and lafaz and fhasahah. Apart from that, this activity tests young children's abilities regarding self-confidence, memory and responsibility with full commitment to something